Mitigation Models and Strategies Corona Virus Disease 2019 (COVID-19) Non-Natural Disasters (Study on BPBD of West Kalimantan Province) - Ul Qadri; Sri Syahbanita Elida; Fitri Larasati (Universitas Muhammadiyah Gorontalo, 2021)
Covid-19 is a non-natural disaster that has shocked countries in the world since the end of 2019 until now and its spread has not been controlled, various efforts have been made by the virus pandemic countries including Indonesia. Its spread occurs in almost every province in Indonesia, one of which is West Kalimantan Province. To prevent the spread of the virus, regional disaster management agencies (BPBD), with various parties, undertake mitigation of its spread and efforts to heal trauma during the pandemic. This study aims to determine the models and strategies of BPBD in mitigation, trauma healing efforts carried out during the pandemic and to find out the obstacles of BPBD in mitigation in West Kalimantan Province. The method used is descriptive qualitative, data sources obtained from interviews with informants, observation and documentation. The analysis technique uses an interactive model by reducing, presenting, drawing conclusions and verification. The results of this study produce models and strategies for mitigating non-natural disasters with a collaborative strategy and a pentahelix approach. Trauma healing efforts have been carried out to provide understanding to the community with preventive measures. The obstacles faced in mitigation include the low level of public awareness in maintaining health protocols and the lack of incomplete SWAB equipment in every district / city.